Effects of Variety Support on Exercise‐Related Well‐Being. Issue 2 (21st April 2016) - Sylvester, Benjamin D.; Lubans, David R.; Eather, Narelle; Standage, Martyn; Wolf, Svenja A.; McEwan, Desmond; Ruissen, Geralyn R.; Kaulius, Megan; Crocker, Peter R.E.; Beauchamp, Mark R.
Abstract : Background: The purpose of this study was to experimentally examine the extent to which variety support in a resistance exercise program influences exercise‐related well‐being among inactive adults. Methods: A sample of 121 inactive university students were randomly assigned and participated in either a high or low variety support 6‐week exercise program. Measures of exercise‐related perceived variety, positive affect, negative affect, and subjective vitality were completed at baseline, after 3 weeks, and after 6 weeks (i.e. post‐test). Results: Through use of structural equation modelling, the results showed that for those who completed measures at post‐test (i.e. n = 55), and for all participants who received variety support (i.e. a modified intention‐to‐treat analysis; N = 121), exercise‐related variety support indirectly explained higher levels of exercise‐related positive affect, and subjective vitality, and lower levels of negative affect, through the mediating role of perceived variety. Conclusions: The provision of variety support in a resistance exercise program influences exercise‐related well‐being through perceptions of variety. Results are discussed in relation to the potential utility of providing variety support to promote exercise‐related well‐being in people who are physically inactive.